Motivational interviewing and oral health education: Experiences from a sample of elderly individuals in North and Northeast Philadelphia. (14th February 2019) - Tellez, Marisol; Myers Virtue, Shannon; Neckritz, Sheryl; Bhoopathi, Vinodh; Hernández, Matilde; Shearer, Barbara
Abstract: Background: Health education has a focus on knowledge dissemination and advice giving, which seldom translates into behavioral changes. Motivational interviewing (MI) has potential for helping elderly patients. However, most oral health studies conducted to date have excluded older individuals, and the outcomes examined have been exclusively clinical. This study examines the treatment fidelity of an individual‐based MI intervention and assesses baseline characteristics related to older adults' self‐efficacy (SE), oral‐health‐related quality of life (OHRQoL), oral health knowledge, and facilitators, barriers, and confidence on achieving MI goals. Methods: A convenience sample of 60 seniors was recruited. Participants were obtained through the flow of patients at dental clinics, and received a 45‐min individual‐based MI education session during a scheduled dental appointment. Results: Regarding MI treatment fidelity, basic proficiency or higher was achieved in all global areas. Significant correlations were found between SE and OHRQoL scores and rating elements of the MI intervention ( P = 0.0001). Lack of knowledge related to connections between poly pharmacy and caries risk, and the importance of use of fluorides were evident. Conclusion: Findings from the study support the reliability of this new MI intervention. Dental professionals are encouraged to adopt the spirit of MI in their one‐on‐one patient counseling.